Postmenopausal women's experiences of a resistance training intervention against vasomotor symptoms: a qualitative study - Emilia Berin; Anna-Clara Spetz Holm; Mats Hammar; Lotta Lindh-Åstrand; Carina Berterö (BMC, 2022)
Abstract Introduction Resistance training may be an effective intervention to improve menopausal symptoms and increase women's quality of life. However, most postmenopausal women do not perform regular resistance training. The purpose of this study was to explore postmenopausal women's experiences of participation in a resistance-training intervention to find barriers and motivators for the training. Methods Fifteen postmenopausal women with low physical activity, who participated in a randomized controlled trial evaluating the effect of a resistance-training program on vasomotor symptoms and health-related outcomes, were consecutively recruited to this qualitative study. After completion of the 15-week resistance-training program, they took part in individual semi-structured interviews, followed by a telephone interview 1 year later. All interviews were transcribed verbatim and thematic analysis was used to analyse the data. Results The analysis generated three themes that were involved at different time points. These were: "Trigger-Hopes of symptom relief", "An evolving motivation as a driving force for change" and "Finding new triggers". Accountability, and continuous professional and emotional support, were factors that fueled the women's motivation to perform regular resistance training during the study. Resistance training improved general well-being and most women experienced improvement in vasomotor symptoms. The women's motivation changed from being driven by a wish to improve bothersome symptoms, into a wish to achieve feelings of well-being and enjoyment. The change was seen regardless of effects of the intervention on vasomotor symptoms. Conclusion This first qualitative evaluation of physical exercise as an intervention to treat vasomotor symptoms in postmenopausal women, found that the symptoms acted as a motivational trigger to initiate resistance training in low-active women. The motivation to exercise changed during the intervention from a wish to ameliorate symptoms into something the women did for enjoyment and well-being in general. This change in motivating factors may have contributed to a behavior change since all participants had increased their physical activity after 1 year regardless of effects on VMS. Trial registration The trial was preregistered at ClinicalTrials.gov; www.clinicaltrials.gov , ID: NCT01987778 , date of first registration: 19/11/2013.